Narratives, Imperatives, and Moral Reasoning - Roland Benabou; Armin Falk; Jean Tirole (Institute of Labor Economics (IZA), 2018)
By downplaying externalities, magnifying the cost of moral behavior, or suggesting not being pivotal, exculpatory narratives can allow individuals to maintain a positive image when in fact acting in a morally questionable way. Conversely, responsibilizing narratives can help sustain better social norms. We investigate when narratives emerge from a principal or the actor himself, how they are interpreted and transmitted by others, and when they spread virally. We then turn to how narratives compete with imperatives (general moral rules or precepts) as alternative modes of communication to persuade agents to behave in desirable ways.
Keywords: D62; D64; D78; D83; D85; D91; H41; K42; L14; Z13; 330; moral behavior; prosocial behavior; narratives; imperatives; justifications; rules; Kantian reasoning; deontology; consequentialism; utilitarianism; norms; organizations